Antibacterial activity of homeopathic medications lycopodium clavatum and arsenicum album against periodontal bacteria = Evaluación antibacteriana de los medicamentos homeopáticos sobre bacterias periodontales - Almaguer Flores, Argelia
There are several controversies regarding the efficacy of homeopathic substances; however, these remedies are used in many countries for the treatment of various pathological conditions. The purpose of this study was to evaluate the in vitro antibacterial activity of two homeopathic tinctures Arsenicum album (mineral extract) and Lycopodium clavatum (plant extract) on the periodontal bacteria Actinomyces israelii, Streptococcus sanguinis, Prevotella intermedia, Aggregatibacter actinomycetemcomitans and Phorphyromonas gingivalis (P. gingivalis). Materials and methods: Equal numbers of bacteria were seeded on agar plates containing enriched media with the homeopathic solutions at 1dH and 1cH dilutions. After 7 days of incubation under anaerobic conditions, colony forming units (CFUs) were counted. The antibacterial effect was calculated based on the total number of CFUs observed on non-tincture containing agar, and on the tincture containing plates. Results: No visible growth of any of the strains was observed on the plates containing Arsenicum album at any of the dilutions tested. In contrast, when Lycopodium clavatum at 1cH dilution was tested, only P. gingivalis was susceptible to this compound. Conclusions: The results suggest that the mineral extract tincture had a greater antibacterial activity than the plant extract tincture, also Lycopodium clavatum preparation could be an effective inhibitor of periodontal pathogens bacteria such as P. gingivalis.